Bahasa budaya: upaya melestarikan jati diri bangsa di era global - Sholihah, Aliya Tus; Rosyidah, Yeni Rofiatin; Rosyidah, Yeni Rofiatin; Khasanah, Arin Safara Nur; Minan, Agus Lathoiful (Maliki Interdisciplinary Journal, 2026)
This article analyzes the role of language and cultural diversity as a foundation for maintaining national identity in the era of globalization. This research uses descriptive qualitative methods. The study reveals that Indonesian functions as a unifying tool for the nation, while cultural diversity becomes an identity that needs to be preserved through local cultural activities and technology. Key challenges include the dominance of foreign languages ​​and the erosion of traditional values, cultural preservation, and the use of digitalization to strengthen national identity. National identity is the result of a dynamic collective effort, combining language, culture, and adaptation to global change. Activities such as cultural festivals, regional language training, and creative communities, so that they feel they have an important role in cultural preservation. Collaboration between the community, traditional leaders, village governments, and cultural institutions is essential to develop a joint strategy for preserving local languages ​​and cultures so that preservation can be carried out effectively, comprehensively, and sustainably.